Comparative Study of Organoleptics Pork from Landrace Pig Fed Based On Landfills Waste with Commercial Feed - I K. W., Sanjaya; Ariana, I N. T.; Sriyani, N. L. P. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
This study aims to find out the comparative quality of organoleptic pork from landrace pigs that are fed to landfill (TPA) waste with meat from landrace pigs fed by commercial feed. The research was conducted in the Laboratory of Animal Product Technology and Microbiology Faculty of Animal Husbandry, Agrokomplek Building of Udayana University. This study used Completely Randomized Design (CRD) with a comparison of two different meat samples. Data analysis was performed by using Mann-Whitney Non-Parametric analysis with the help of SPSS 24. Organoleptic variables observed in this study include color, aroma, texture, tenderness, taste and overall acceptance. The treatment consisted of meat from landrace pigs fed on landfill waste with meat from landrace pigs fed by commercial feed. From the result of the research, it is found that panelist's favorite level of color, texture, tenderness and meat flavor of landfill pigs are fed significantly (P<0.05) with pigs given commercial feed. While the panelist's favorite level of landrace pigs aroma given by landfill-based waste feed was statistically not significantly different (P>0.05) with commercially fed pigs. Based on the results of this study it can be concluded that meat from landrace pigs fed on landfill waste has lower organoleptic quality compared to meat from landrace pigs fed by commercial feed. Key words :  Landrace Pigs , Meat Quality , TPA.